2011
DOI: 10.1007/978-3-642-20847-8_42
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Advertise: How Many Ads Are Enough?

Abstract: Sponsored advertisement(ad) has already become the major source of revenue for most popular search engines. One fundamental challenge facing all search engines is how to achieve a balance between the number of displayed ads and the potential annoyance to the users. Displaying more ads would improve the chance for the user clicking an ad. However, when the ads are not really relevant to the users' interests, displaying more may annoy them and even "train" them to ignore ads. In this paper, we study an interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…This motivated research that investigated whether any ads should be displayed at all [3]. It is also easy to see that a similar and related problem formulation is to determine how many ads should be displayed to the users [16]. Moreover, determining the optimal number of ranked results is also important in a number of other IR applications such as legal e-discovery [14], where there is an significant financial or labor cost associated with reviewing results.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This motivated research that investigated whether any ads should be displayed at all [3]. It is also easy to see that a similar and related problem formulation is to determine how many ads should be displayed to the users [16]. Moreover, determining the optimal number of ranked results is also important in a number of other IR applications such as legal e-discovery [14], where there is an significant financial or labor cost associated with reviewing results.…”
Section: Related Workmentioning
confidence: 99%
“…While much of the work in information retrieval has been centered around ranking, there is growing interest in methods for ranked list truncation -the problem of determining the appropriate cutoff of candidate results [1,9]. This problem has garnered attention in fields like legal search [14] and sponsored search [3,16], where there could be a monetary cost for users looking into an irrelevant tail of documents or where showing too many irrelevant ads could result in ad blindness. The fundamental importance of this problem has led to development of methods that are automatically able to learn in a data-driven fashion [9].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there has been research that investigated whether it is possible to determine whether any ads should be returned to the user or not (Broder et al, 2008). A similar problem formulation investigated how many ads should be returned to the users (Wang et al, 2011a). Determining the optimal number of results to return is also important in a number of other search tasks, including legal e-discovery (Tomlinson et al, 2007), where there is an immense cost associated with reviewing results.…”
Section: Modeling Relevance Scoresmentioning
confidence: 99%
“…Moreover, Dembczyński et al demonstrated how their suggested algorithms can be used to provide recommendations in order to improve the ads' quality. Later in 2011, Wang et al [33] attempted to predict the ideal number of ads that should be displayed for a given searchengine query.…”
Section: Ad Success Predictionmentioning
confidence: 99%